2017
DOI: 10.1002/jcc.25074
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the DFT method to study expanded porphyrins with different topologies

Abstract: Meso-aryl expanded porphyrins present a structural versatility that allows them to achieve different topologies with distinct aromaticities. Several studies appeared in the literature studying these topological switches from an experimental and theoretical point of view. Most of these publications include density functional theory calculations, being the B3LYP the most used methodology. In this work, we show that the selection of the functional has a critical role on the geometric, energetic, and magnetic resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
96
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 114 publications
10
96
0
Order By: Relevance
“…The geometry of all systems was optimized with the method PBE0/Def2TZVP . It is known that PBE0 functional could overestimate aromaticity but in the present study, we analyze trends that should not be affected by this issue . Moreover, recent studies have shown that PBE0 is one of the functional that does not have large errors in the calculation of atomic densities.…”
Section: Methodsmentioning
confidence: 99%
“…The geometry of all systems was optimized with the method PBE0/Def2TZVP . It is known that PBE0 functional could overestimate aromaticity but in the present study, we analyze trends that should not be affected by this issue . Moreover, recent studies have shown that PBE0 is one of the functional that does not have large errors in the calculation of atomic densities.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have demonstrated that functionals with a high percentage of Hartree‐Fock (HF) exchange (eg, M06‐2X, CAM‐B3LYP, becke‐half‐and‐half‐LYP (BHandHLYP), etc.) give better results for the conjugated (and, therefore, aromatic) systems . Hence, functional with higher Hartree‐Fock exchange: BH and HLYP and M06‐2X are also considered to check the consistency.…”
Section: Methodsmentioning
confidence: 99%
“…
The N-heterocyclic carbene, imidazole-2-ylidene, and its main group (13)(14)(15) analogues contain cyclically conjugated 6π electrons. Experimental 1 H nuclear magnetic resonance (NMR) spectra suggest an increase in aromaticity along a period from left to right.
…”
mentioning
confidence: 99%
See 2 more Smart Citations